2021
DOI: 10.1080/09613218.2021.1905501
|View full text |Cite
|
Sign up to set email alerts
|

The impact of policy instruments on the first generation of Tall Wood Buildings

Abstract: In a context of environmental concern and limited urban land, the construction industry faces the challenge of providing solutions for the increasing urban population both efficiently and sustainably. Numerous innovations on engineered wood products for multistorey buildings arise as one of the most promising solutions. In this context, various policies have facilitated the development of Tall Wood Buildings (TWBs). Yet, few publications analyse these policies and their influence on specific projects. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…It focuses on three analysis lenses: (i) structural limitation, (ii) envelope systems, and (iii) architectural massing. Wiegand's master's thesis in 2019 [37] examines the effects of policies on 49 case studies linked with CTBUH structural systems, and graphically displays the division, his later 2021 paper deals with the same topic on a set of 47 tall timber buildings [38]. The 2021 study by Žegarac Leskovar et al [39] contains only a list of 31 MSTB projects, and creates four lenses of examination: architectural, environmental, energy, and structural, based on previous literature [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It focuses on three analysis lenses: (i) structural limitation, (ii) envelope systems, and (iii) architectural massing. Wiegand's master's thesis in 2019 [37] examines the effects of policies on 49 case studies linked with CTBUH structural systems, and graphically displays the division, his later 2021 paper deals with the same topic on a set of 47 tall timber buildings [38]. The 2021 study by Žegarac Leskovar et al [39] contains only a list of 31 MSTB projects, and creates four lenses of examination: architectural, environmental, energy, and structural, based on previous literature [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is assured by (58), who confirmed that prefabricated buildings provide more environmental benefits than on-site construction, i.e., essentially in terms of waste generation, materials and energy consumption, and carbon emissions. Moreover, (59) argued that engineered wood products arise as promising solutions to increase the efficiency and sustainability of the innovative construction. Therefore, companies must adapt their culture and processes to society's demands, since an innovative organization will undoubtedly generate long-term value and will be In general, when the construction of a green building is planned, it requires about 10 % additional costs, yet it should offer more than 50 % energy and water savings over its lifecycle (61).…”
Section: Basic Unitary Costs Of Timber Houses Produced In Brazilmentioning
confidence: 99%
“…The latter allowed the industry to manufacture products with improved uniformity, greater efficiency, and dimensional stability 29 . Since the construction of the first 8-storey wood buildings in the late 2000s, the building industry has completed around 50 projects over six storeys globally, leaping from 8 to 24 stories in 12 years (Figure 3) 30 .…”
Section: Social Sustainabilitymentioning
confidence: 99%